The study of antibacterial activity of Hibiscus sabdariffa flowers extracts - Fitua M. Aziz; Ayad M. R. Raauf; Shaimaa I. Shukur (College of Pharmacy / Mustansiriyah University, 2012)
The aqueous and methanol extracts obtain from flowers Hibiscus sabdariffa have been investigated for their antibacterial activity. Antibacterial activity was determined by using agar well diffusion method at concentrations of (500, 250, 125, 62.5) mg/ml, against Staphylococcus aureus, Escherichia coli, Salmonella typhi, Klebsiella pneumonia, Enterococcus spp., Acinetobacter spp., Pseudomonas aeruginosa, Shigella dysenteriae, Proteus vulgaris. Hibiscus sabdariffa extracts demonstrated antibacterial effects of methanol and aqueous extracts against bacteria used in this study at different levels. Only E. coli was not susceptible to aqueous extract at all concentrations were used.